Tools for the job - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Tools for agriculture - a guide to appropriate equipment for smallholder farmers 256pp ISBN 1 85339 100 X Pbk price UKL30.00 published by CTA and Intermediate Technology Publications, 103- 105 Southampton Row London WC1B 4HH, UK Available from